Optimazation and performance analysis of gas turbine blade by implimenting cooling techniques - Patel, Rajendra Kumar; Thakare, Pariwesh; Sahu, Dhananjay kumar; Suryawanshi, Aakanksha (Recent Research in Science and Technology, 2014)
Gas turbine are extensively used for aircraft propulsion, land-based power generation, thermal efficiency and power output of gas turbine increase with increasing turbine rotor inlet temperature (RIT) the current RIT level in advanced gas turbine is far above the melting point of the blade material. Therefore, along with high temperature material developed a sophisticated cooling scheme must be developed for continuous safe operation of gas turbine with high performance ,gas turbine blades are cooled internally and externally for increase the life of blade turbine. This paper is focused on internal cooling of blade and vanes on gas turbine, internal cooling is achieved by passing the coolant through several enhanced serpentine passages inside the blade and extracting the heat from the outside of the blade. Jet impingement cooling, rib tabulators, dimple and pin fin cooling are all utilized as method of internal cooling, which are presented in this article. Due to the different heat transfer enhancement and pressure drop, they are used in specific part of the blades and vanes on the gas turbine.